Partizipation als Voraussetzung der Bildung des Demokratischen: Zur Akzeptanz der Kinderrechte in der Haltung von Erwachsenen - Benischek, Isabella (Österreichisches Religionspädagogisches Forum, 2025)
Democracy requires, as its foundation, a political culture sustained by a unifying ethos. Among the essential elements of such a culture are human rights as well as children’s rights. As part of an empirical-quantitative research project at the University College of Teacher Education Vienna/Krems, student teachers, educators, and citizens were surveyed regarding their acceptance of children’s rights.